Exploring individual differences among teachers’ ICT acceptance: A path model and role of experience - Monacis, Lucia; Limone, Pierpaolo; Ceglie, Flavio; Tanucci, Giancarlo; Sinatra, Maria (Human Technology, 2019)
This research tested a path model in which constructive beliefs, components of the technological acceptance model, and perceived enjoyment directly and indirectly predicted information and communication technology (ICT) integration into educational practices. We analyzed whether experience played a moderating role in this nomological network of associations. The sample comprised 374 Italian teachers (Mage = 38.69, SD = 5.30, F = 198) divided into two groups: the first with 20 or fewer years of teaching experience and the second with 21 or more years. They completed a questionnaire comprising a socioanagraphic section and the following scales: the Teacher’s Beliefs, the Intrinsic Motivation, the Extrinsic Motivation, the Perceived Ease of Use, the Behavioral Intention to Use Computer and the ICT Class Use. Results showed positive correlations between ICT integration and the variables of interest and generally confirmed the mediated and moderated relationships. Suggestions were provided to enhance a successful ICT integration.